TRANSFER COMPANY IN LAW NUMBER 11 YEAR 2020 CONCERNING WORK CREATION - RIZA FAHLAPI; Ario Fahmi Muhamad; Lukman Hakim; Adhi Lingga Harymurti; Baskara Agung Wibawa (Fakultas Hukum Universitas Djuanda Bogor, 2022)
Outsourced companies as supporting companies in companies (service providers) in running their business for the management of Outsourcing (TAD) became very competitive after the issuance of Law Number 11 of 2020 (Job Creation) concerning manpower according to Law no.13 2003. The position of workers in this law includes the existing regulations on matters for amendments, deletions and additions in the work creation law. In carrying out their business, the outsourcing worker's work relationship is with the Employer Service Provider, which is placed at the Service Provider Company, which is regulated in more detail for their rights and obligations to the Placement Company where the worker is placed.